Analysis of international trade, exchange rate and crude oil price on economic development of Yunnan Province: A GARCH-Vine copula model approach - Xinyu Yuan (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. In this paper, we attempted to use the GARCH-vine copula model to analyze the dependence structure of international trade, exchange rate, and crude oil price on the economic development of Yunnan Province. In the C-vine, the df of the student-t copula model is significant on C14and C25|1, and there is the least degree of freedom in C14, which means that there is a greater probability of extreme values in industrial added value and export. In the Clayton copula, we find a strong significance with fminunc in C13and C45|123. With fminunc in C13, the Clayton copula can catch left tail dependence. This means that a decrease in the crude oil spot price is inclined to retard Yunnan's industrial added value growth. In the D-vine, we find that the df of the student-t copula model varies considerably and significantly in C23and C34, respectively. Finally, in the Clayton copula, we conclude that there exists a strong significance with fminunc in C45(export-import) and C13|2.